Development of crane load codes on the basis of experimental research - Pichugin, Sergii (Academic journal Industrial Machine Building Civil Engineering, 2022)
The buildings and structures reliability and safety largely depend on a proper understanding of the nature and quantitative description and rationing of loads on building structures, including crane loads. Most of the parameters of the crane load codes have a probabilistic nature and require the use of statistical methods to substantiate them. These methods are constantly changing and evolving together with the regular revision of building design codes. Analysis of domestic codes' evolution of crane load together with their statistical substantiation is an urgent task, which is this article's purpose. Since the late 1930s, leading construction research institutes and universities have conducted research on crane loads, which results have been consistently incorporated into design codes. Giving an overall assessment of Ukrainian crane loads standards, it should be emphasized that they are compiled on a modern methodological basis, close to European standards Eurocode, based on representative statistics, more differentiated, and have a scientific probabilistic nature.
Keywords: building design codes; bridge crane; overhead crane; crane load; normative load; design load